Trainwreck: The End of the Conservative Revolution (and Not a Moment Too Soon) - Press Bill (Wiley, 2008)
In a domestic cooptation of the neocon “End of History” thesis, talk radio host Press (Spin This!) argues that conservatism's record of failure should condemn it to a subordinate place in American politics—it can survive to check “the excess of the majority,” argues Press, but must never again be allowed to govern. For Press (who unfurls a dishonor roll of scandals, policy failures, corporate toadying, double standards and outright criminality), this betrayal of public trust has meant the betrayal of conservatism's own purported principles. Thus, citing the conservative “canon” of the mid-century right-wing intellectual Russell Kirk, and even Barry Goldwater, Press lambastes Bush, Cheney and other Republicans for turning away from the ideals of small government and limited executive power. Likewise, on the environment, conservatism was formerly synonymous with conservation, notes Press, pointing to early Republican leadership on this score from Teddy Roosevelt to California state senator and “environmental pioneer” Peter Behr. These contradictions rarely come as revelations—indeed the bulk of this narrative will be familiar to anyone paying even passing attention to the news—but by presenting all this material together, Press creates a serviceable election-year handbook for voters, particularly the Democratic opposition. (Apr.) (Publishers Weekly, January 28, 2008)